KEPALA SEKOLAH SEBAGAI EDUKATOR DALAM MENINGKATKAN KOMPETENSI GURU PADA SMK NEGERI 2 SIGLI KABUPATEN PIDIE - Farizal Hadi; Cut Zahri Harun; Sakdiah . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The principal as an educator has a strategic role in enhancing the teachers’ competence. The purpose of this study was to investigate the program, the principal’s strategies, the factors that influence and obstacles faced by principal as an educator in improving the teachers’ competence at Vocational School (SMK) No 2 of Sigli, Pidie Regency. This research used the descriptive method with a qualitative approach. Data collection techniques used was observation, interviews, and documentation. The research subjects in this study were a principal and teachers. The results showed that (1) The principal has carried out his role as an educator in improving the competence of teachers were to coach and mentor to teachers in the learning process, to conduct training, to provide mental and moral guidance of teachers, to provide encouragement and motivation to teachers; (2) The strategy of principal as an educator in improving the competence of teachers was by providing an understanding of the importance of the task which raised awareness of their own to do a good job. To face the teachers, principals usually always regarded teachers as partners, so that the principal could consult, discuss and exchange ideas with teachers, so it was found an effective way to improve the teachers’ competence; (3) Factors that influence the principal as educators were the commitment of teachers to the task given by the principal, disciplinary and exemplary principals; and (4) The obstacles faced by the principals as educators were the lack of responsibility of teachers in performing their duties and less than the maximum in the division of work.Keywords: principal, educator and teachers’ competence.